Tính \(\frac{x-y}{x+y}\) biết \(x^2-2y^2=xy\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(P=\left[\left(\frac{x-y}{2y-x}-\frac{x^2+y^2+y-2}{x^2-xy-2y^2}\right):\frac{4x^4+4x^2y+y^2-4}{x^2+y+xy+x}\right]:\frac{x+1}{2x^2+y+2}\)
\(P=\left[\left(\frac{x-y}{2y-x}-\frac{x^2+y^2+y-2}{\left(x+y\right)\left(x-2y\right)}\right):\frac{\left(2x^2+y+2\right)\left(2x^2+y-2\right)}{\left(x+y\right)\left(x+1\right)}\right]:\frac{x+1}{2x^2+y+2}\)
\(P=\left(\frac{\left(x-y\right)\left(x+y\right)+x^2+y^2+y-2}{\left(x+y\right)\left(2y-x\right)}.\frac{\left(x+y\right)\left(x+1\right)}{\left(2x^2+y+2\right)\left(2x^2+y-2\right)}\right):\frac{2x^2+y+2}{x+1}\)
\(P=\left(\frac{2x^2+y-2}{2y-x}.\frac{x+1}{2x^2+y-2}\right).\frac{1}{x+1}\)
\(P=\frac{1}{2y-x}\)
Tại \(x=-1,76\) và \(y=\frac{3}{25}\) thì giá trị của \(Q=\frac{1}{2}\)
Đặt \(A=\frac{x-y}{2y-x}-\frac{x^2+y^2+y-2}{x^2-xy-2y^2}\)
\(B=\frac{4x^4+4x^2y+y^2-4}{x^2+y+xy+x}\)
\(C=\frac{x+1}{2x^2+y+2}\)
Ta có:
A = \(\frac{x-y}{2y-x}-\frac{x^2+y^2+y-2}{x^2-y^2-xy-y^2}=\frac{x-y}{2y-x}-\frac{x^2+y^2+y-2}{\left(x-2y\right)\left(x+y\right)}=\frac{\left(x-y\right)\left(x+y\right)+x^2+y^2+y-2}{\left(2y-x\right)\left(x+y\right)}\)
=>A=\(\frac{x^2-y^2+x^2+y^2+y-2}{\left(2y-x\right)\left(x+y\right)}=\frac{2x^2+y-2}{\left(2y-x\right)\left(x+y\right)}\)
B=\(\frac{\left(2x^2\right)^2+2.2x^2.y+y^2-4}{x^2+xy+x+y}=\frac{\left(2x^2+y\right)^2-4}{x\left(x+y\right)+\left(x+y\right)}=\frac{\left(2x^2+y+2\right)\left(2x^2+y-2\right)}{\left(x+1\right)\left(x+y\right)}\)
=>\(P=\left(A:B\right):C\)
\(=\left[\frac{2x^2+y-2}{\left(2y-x\right)\left(x+y\right)}:\frac{\left(2x^2+y+2\right)\left(2x^2+y-2\right)}{\left(x+y\right)\left(x+1\right)}\right]:\frac{x+1}{2x^2+y+2}\)
\(=\frac{2x^2+y-2}{\left(2y-x\right)\left(x+y\right)}.\frac{\left(x+y\right)\left(x+1\right)}{\left(2x^2+y+2\right)\left(2x^2+y-2\right)}.\frac{2x^2+y+2}{x+1}\)
\(=\frac{1}{2y-x}\)
=>\(P=\frac{1}{2y-x}\)
Thế x=-1,76 và y=3/25 vào P
=>\(P=\frac{1}{2.\frac{3}{25}-1,76}=\frac{1}{2}\)
\(=\left(\dfrac{x-y}{2y-x}-\dfrac{x^2+y^2+y-2}{x^2-2xy+xy-2y^2}\right):\dfrac{\left(2x^2+y\right)^2-4}{x\left(x+y\right)+\left(x+y\right)}:\dfrac{x+y}{2x^2+y+2}\)
\(=\left(\dfrac{x-y}{2y-x}-\dfrac{x^2+y^2+y-2}{\left(x-2y\right)\left(x+y\right)}\right)\cdot\dfrac{\left(x+y\right)\left(x+1\right)}{\left(2x^2+y+2\right)\left(2x^2+y-2\right)}\cdot\dfrac{2x^2+y+2}{x+y}\)
\(=\dfrac{y^2-x^2-x^2-y^2-y+2}{\left(x-2y\right)\left(x+y\right)}\cdot\dfrac{x+1}{2x^2+y-2}\)
\(=\dfrac{-\left(2x^2+y-2\right)}{\left(x-2y\right)\left(x+y\right)}\cdot\dfrac{x+1}{2x^2+y-2}=\dfrac{-\left(x+1\right)}{\left(x-2y\right)\left(x+y\right)}\)
\(\left(\frac{x-y}{2y-x}-\frac{x^2+y^2+y-2}{x^2-xy-2y^2}\right):\frac{4x^4+4x^2y+y^2-4}{x^2+y+xy+x}:\frac{1}{2x^2+y+2}\)
\(=\left(\frac{x-y}{2y-x}+\frac{x^2+y^2+y-2}{\left(x+y\right)\left(2y-x\right)}\right):\frac{\left(y+2x^2+2\right)\left(y+2x^2-2\right)}{\left(x+1\right)\left(x+y\right)}:\frac{1}{2x^2+y+2}\)
\(=\frac{y+2x^2-2}{\left(x+y\right)\left(2y-x\right)}.\frac{\left(x+1\right)\left(x+y\right)}{\left(y+2x^2+2\right)\left(y+2x^2-2\right)}.\left(2x^2+y+2\right)\)
\(=\frac{\left(x+1\right)}{\left(2y-x\right)}\)
Ta có : \(x^2-2y^2=xy\)
\(\Leftrightarrow x^2-2y^2-xy=0\)
\(\Leftrightarrow x^2+xy-2y^2-xy=0\)
\(\Leftrightarrow x.\left(x+y\right)-2y.\left(x+y\right)=0\)
\(\Leftrightarrow\left(x+y\right).\left(x-2y\right)=0\)
Mà x+y khác 0 nên \(x-2y=0=>x=2y\)
\(\Rightarrow\frac{x-y}{x+y}=\frac{2y-y}{2y+y}=\frac{y}{3y}=\frac{1}{3}\)